(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This study investigates the role of political leadership in enhancing accountability for health budget expenditures in Ubungo Municipality, Tanzania. Employing a cross-sectional survey design, data were collected from 400 respondents using questionnaires. The research specifically examined community awareness of health budget information, perceptions of political accountability, and the degree of political engagement in public health oversight. The findings revealed a significant gap in public awareness: 75% of respondents indicated that political leaders do not disseminate adequate information regarding health service improvements. Similarly, 55% of respondents disagreed that political leaders make the community aware of health budget expenditures. While some leaders emphasized their role in tax advocacy and service monitoring, inconsistencies in communication and community engagement were evident. Only a minority reported frequent community meetings or transparent budget disclosures. These findings suggest that although political leaders in Ubungo engage in some accountability-enhancing practices—such as advocating for tax compliance and expanding health service infrastructure—their roles in transparent budget oversight remain underutilized. The study concludes that political accountability in health service delivery is constrained by limited information-sharing practices and a lack of institutionalized citizen engagement platforms. It recommends adopting integrated leadership strategies that promote fiscal transparency, empower communities through regular communication, and institutionalize accountability mechanisms within the decentralized health governance framework.